Analisis Semiotika Roland Barthes pada Iklan IKEA: Second Best di Kanal YouTube Ads of Brands - Christina Nur Wijayanti; Wahjoe Mawardiningsih; Mathilda Regina Maharani I; Hafizh Harfiansyah (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
This study discusses the interpretation of semiotic theory in an advertisement, specifically focusing on IKEA's